Utility of 2,2׳- Bipyridyl Reagent in Spectrophotometric Assay of Acetylcysteine in Pure Form and in Its Pharmaceutical Preparations - Shahad Hasan; Saad Sultan (College of Education for Pure Sciences, 2022)
This study includes development of a sensitive spectrophotometric method for the determination of acetylcysteine in aqueous solution. The method is based on the oxidation of acetylcysteine with a ferric ion, followed by reacting of produced ferrous ion with 2,2׳-bipyridyl to form a pink complex , which is stable and water-soluble and has the highest absorption at a wavelength of 524 nm. The limits of Beer's law were in the concentration range of (5-180) µg of acetylcysteine in a final volume of 20 milliliters (0.25-9.0 µg.ml-1) and the molar absorptivity of 8633.28 L. mol-1 .cm-1 , Sandell's sensitivity index of 0.0189 µg.cm-2. The relative error of -4.28% - 4.98 % and relative standard deviation of ± 0.56% - ± 3.75% depending on the concentration level. The limit of detection limit(LOD) and limit of quantitation (LOQ) were calculated and equal to 0.01837 and 0.06124 µg/ml respectively, no inference was observed in the common pharmaceutical excipients. The results obtain by proposed method were in good agreement with those obtain from official British pharmacopoeia using t-test (at 95% confidence limit) which indicates that there is no significant differences between them. The method was successfully applied to determine acetylcysteine in its pharmaceutical preparations.